2011
DOI: 10.2741/e271
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine enhances proliferation in transplanted rat fetal epiglottis

Abstract: Fetal rat epiglottis and its developmental potential in ectopic transplants under the influence of the epigenetic drug was investigated. Epiglottises from 17-days-old rat embryos were transplanted under kidney capsules of adult rats for 14 days. 5-azacytidine (5 mg/kg) was injected intraperitoneally during first three days and controls were sham treated. TEM, immunohistochemical detection and quantitative stereological analysis of the Proliferating Cell Nuclear Antigen (PCNA) expression (numerical density N(v)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Although its immunohistochemistry levels in rat renewing tissues were found to be higher than those of other cell proliferation markers, those markers sometimes could not be visualized due to technical problems (21). In our current experiments, in the same way as in previously published studies (9,10,15), PCNA signal was always easily detected. The quantitative difference in its expression (Nv), found between experimental and control groups of limb buds, was in accordance with the results obtained by measurements of the overall explant growth.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Although its immunohistochemistry levels in rat renewing tissues were found to be higher than those of other cell proliferation markers, those markers sometimes could not be visualized due to technical problems (21). In our current experiments, in the same way as in previously published studies (9,10,15), PCNA signal was always easily detected. The quantitative difference in its expression (Nv), found between experimental and control groups of limb buds, was in accordance with the results obtained by measurements of the overall explant growth.…”
Section: Discussionsupporting
confidence: 86%
“…However, during in vitro culture, vasculogenesis found in 13 days old isolated limb buds seems to have disappeared. The reason for this was probably the lack of specific in vivo signals, which are absent from the simple in vitro environment (15). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the negative 5azaC activity on cell proliferation in the limb bud as an immature whole organ, we showed that proliferation of the vertebral cartilage was increased by 5azaC, similarly as in 17-day-old fetal epiglottis of the same strain of rats transplanted in vivo [65]. The 5azaC-induced hypomethylation also reversed the aged phenotype of the adult mesenchymal stem cells by enhancing cell proliferation [59].…”
Section: Discussionmentioning
confidence: 99%